Preventing systemic crises through bank transparency - Ari Hyytinen; Tuomas Takalo (Bank of Finland, 2003)
The banking system is known to be vulnerable to self-fulfilling crises that are caused by depositors coordination failure.We show that transparency regulation may prevent certain types of systemic crises by eliminating the possibility of the coordination failure.
URN:NBN:fi:bof-20140807541
Keywords: G21; G28; 330; bank transparency; financial stability; disclosure regulation